Differences in physiological responses during wheelchair basketball matches according to playing time and competition - Iturricastillo, A.; Granados, C.; Camara, J.; Reina, R.; Castillio, D.; Barrenetexea, I.; Lozano, L.; Yanci, J. (Research Quarterly for Exercise and Sport, 2018)
Purpose: The main purpose of the present study was to determine physiological responses in wheelchair basketball (WB) matches in relation to heart rate (HR), match load (ML), differentiated perceived exertion (dRPE), lactate concentrations (LA), and tympanic temperature (TEMP), while specifying the individual player's playing time during different types of matches.